Intensity Modulated Arc Therapy in Bilaterally Irradiated Head and Neck Cancer: A Comparative and Prospective Multicenter Planning Study. (28th May 2014) - Vernat, Stéphanie Servagi; Ali, David; Messina, Caroline; Pommier, Pascal; Dussart, Sophie; Puyraveau, Marc; Viard, Romain; Lacornerie, Thomas; Lisbona, Albert; Fenoglietto, Pascal; Mazurier, Jocelyne; Garcia, Robin; et al.
<x xml:space="preserve">Abstract</x> A dosimetric comparison was made of Helical Tomotherapy (HT) and Rapid'Arc® (RA) in 115 patients with head and neck carcinoma included in a prospective and multicentric study. HT and RA provided highly conformal plans that easily complied with dose volume constraints for organs at risk. HT reduced high doses to the planning target volumes (PTVs) compared to RA and provided a more homogeneous dose distribution but with an increased Non Tumoral Integral Dose (NTID) than RA. However, the clinical consequences of these dosimetric advantages and disadvantages need further investigation.